(untitled) (Al-Qamar, 2020)
By faith almost Pashtoon are Muslim so it is by certain natural for them that they have an unconditional love for Islam. Their love for Islam is pure that cannot be paralleled by any other love. It is due to this reason that the Pashtoon have contributed a lot in Spreading the Holy Message of Quran, unfolding the wisdom and spiritualism contained in the saying, of the Holy Prophet (PBUH) and interpretation of the Islamic Jurisprudence. The most ancient and paobably the first ever book, that vividly describes the life style of the Holy Prophet (SAW) is Qalbus-Sair authored by Gohar Khan Khattak. Gohar Khan Khattak is the son of great Pashto Poet, Khushal Khan Khattak, himself was a great poet and literary artist. In order to make Pashtoon nation fully understand the message embodied in teachings and deeds of the Holy Prophet (SAW). Gohar Khan Khattak wrote this rare and authentic book of Seerat. The book is quite comprehensive in rational and religious perspective which gives an easy understanding of the Holy life of the Holy Prophet (SAW). This book contains verses from the Holy Quran worthy sayings (Hadiths) of the Holy Prophet story from the early bright period of Islam and poetry which are studied in the book. These references aptly make the book one of the authentic and widely accepted on Seerat.